2017
DOI: 10.3390/atmos8070130
|View full text |Cite
|
Sign up to set email alerts
|

Passive Sampling and Analysis of Naphthalene in Internal Combustion Engine Exhaust with Retracted SPME Device and GC-MS

Abstract: Exhaust gases from internal combustion engines are the main source of urban air pollution. Quantification of Polycyclic aromatic hydrocarbons (PAHs) in the exhaust gases is needed for emissions monitoring, enforcement, development, and testing of control technologies. The objective was to develop quantification of gaseous naphthalene in diesel engine exhaust based on diffusion-controlled extraction onto a retracted solid-phase microextraction (SPME) fiber coating and analysis on gas chromatography-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…To date, all published research on TWA-SPME has used Equation (1) as the basis of quantification [ 3 , 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] of VOCs in an outdoor air, laboratory air, pyrolysis reactor air, engine exhaust, and process air. Equation (1) predicted measured gas concentrations with reasonable accuracy and precision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all published research on TWA-SPME has used Equation (1) as the basis of quantification [ 3 , 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] of VOCs in an outdoor air, laboratory air, pyrolysis reactor air, engine exhaust, and process air. Equation (1) predicted measured gas concentrations with reasonable accuracy and precision.…”
Section: Introductionmentioning
confidence: 99%
“…Woolcock et al [ 17 ] reported a significant departure from the zero-sink assumption and from Equation (1) suggesting “apparent” diffusion coefficient ( D ) dependent on both sampling time ( t ) and retraction depth ( Z ). Baimatova et al [ 11 ] reported significant differences in the extracted mass of naphthalene gas for different SPME coatings, i.e., that Equation (1) does not incorporate. Recent research by Tursumbayeva [ 20 ] shows that the discrepancy between Equation (1) and experimental data are amplified when a wide-bore glass liner is used for passive sampling with SPME fiber retracted inside it.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of analyte concentration in the air near the fiber tip results in the decrease of the analyte flux (i.e., the mass of analyte entering protecting needle per cross-sectional area and time) from the sampled air with time. This affects the sampling rate, which was previously assumed to be constant [3,4,[8][9][10][11][12][13][14][15][16][17].…”
Section: Twa Sampling Profiles Of Benzene From Air Using Different Comentioning
confidence: 99%
“…To date, all published research on TWA-SPME used Eq. 1as the basis of quantification [3,4,[8][9][10][11][12][13][14][15][16][17] of VOCs in laboratory air, pyrolysis reactor air, engine exhaust, and process air. Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation